DEVELOPING INTEGRATIVE THEMATIC MATERIALS BASED ON LOCAL WISDOM ON SCIENCE SUBJECT OF THEME 3, HEALTHY FOOD, AT GRADE V - Ahmad Shofa; Su’ad Su’ad; Murtono Murtono (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The objectives of this study were 1) to analyze teachers’ input to develop Integrated Thematic Materials Based on Local Wisdom on Science subject Theme 3: Healthy Food, for Grade 5 Elementary School, 2) to find out how to prepare Integrated Thematic Materials Based on Local Wisdom for Science subject Theme 3: Healthy Food, for Grade 5 Elementary School , and 3) to reveal the effectiveness of the Integrated Thematic Materials Based on Local Wisdom on Science Subject Theme 3: Healthy Food, for Grade 5 Elementary School. This research was Research and Development (R & D) adapted from Sugiyono including ten steps. The validation of teaching materials wascarried out by proficient material experts and media experts. The results showed that the products in this development research were declared feasible and effective to be used as supporting teaching materials for grade V. The feasibility of this thematic module product was based on the validation results of material experts which obtained a total score of 73 in very good category and the results of validation by media experts which obtained a total score of 116 in very good category. The feasibility of the thematic module product was also strengthened by the results of the effectiveness test (N-Gain) on the product trial which obtained a score of 85.2968 or 85.30% in effective category for the experimental class, and the effectiveness test (N-Gain) on the trial which obtained a score of 88, 5386 or 88.54% with the effective category.